Evaluation of Mosque Library Governance Based on National Special Library Standards Number 7 of 2022 at the Mujahidin Grand Mosque Library, Pontianak - Sahidi, Sahidi; Riska, Riska; Rahman, Miftah (Universitas Negeri Padang, 2024)
The objective of this study is to evaluate the implementation of the National Standard for Special Libraries No. 7 of 2022 concerning worship house libraries at the Library of Masjid Raya Mujahidin Pontianak. The research employs a qualitative method with a descriptive case study approach focused on the implementation of the standard. Data collection techniques include interviews and observations, with interviews conducted with library managers. The findings reveal that the Library of Masjid Raya Mujahidin Pontianak has successfully met several prescribed standards, particularly in terms of collection provision and the availability of library staff. However, several indicators of the National Standard for Special Libraries No. 7 of 2022 have not yet been implemented, such as the provision of computer technology facilities, the absence of library promotion activities, and the lack of written policies on library management in accordance with the mandates of the standard. Key challenges include the absence of dedicated staff, limited technological facilities, unimplemented library standards, insufficient collection development, and minimal collaboration with external parties.